Prospects of artificial tree for solar desalination. (September 2019) - Mi, Baoxia; Finnerty, Casey; Conway, Kelly
Abstract : Seawater and brackish water desalination provides a viable alternative to clean water supply for regions lacking fresh water sources or facing severe droughts. Current desalination technologies, however, are energy-expensive and environmentally unfriendly. Mimicking the natural transpiration process of mangrove trees that are able to survive in high-salinity environment, an artificial tree is conceived as a next-generation desalination system that can be entirely solar-powered and potentially achieve zero-liquid discharge and resource recovery. The artificial tree will float on saline water and be composed of synthetic roots that uptake and pretreat feed water, a synthetic trunk that lifts water up via capillary action through its microporous xylem, and synthetic leaves that efficiently convert sunlight to localized heat for water evaporation through their pores. Water vapor is condensed for clean water production while salt is collected for resource recovery or proper disposal. Science and technologies available and needed for realizing the artificial tree system are critically reviewed.